B-mode ultrasonography and ARFI elastography of articular and peri-articular structures of the hip joint in non-dysplastic and dysplastic dogs as confirmed by radiographic examination - Carneiro, Rafael Kretzer [UNESP]; da Cruz, Igor Cezar Kniphoff; Gasser, Beatriz; Lima, Bruna [UNESP]; Aires, Luiz Paulo Nogueira [UNESP]; Ferreira, Márcio Poletto; Uscategui, Ricardo Andres Ramirez; Giglio, Robson Fortes; Minto, Bruno Watanabe [UNESP]; Rossi Feliciano, Marcus Antônio (Springer Nature, 2023)
Background: Canine hip dysplasia is a common orthopedic disease in veterinary practice. The diagnosis is made by radiographic examinations that evaluate bone alterations associated with hip dysplasia. Although radiographic examination is the gold standard for diagnosis, it does not allow a detailed evaluation of soft tissues such as the joint capsule and periarticular muscles. This study aimed to evaluate the accuracy of B-mode ultrasonography and acoustic radiation force impulse (ARFI) elastography in assessing the joint capsule and periarticular muscles of dogs using the Orthopedic Foundation of Animals (OFA) classification and the distraction index (DI) in the early and late diagnosis of hip dysplasia. This study sought to propose a protocol for the ultrasonographic evaluation of the structures involved in canine hip dysplasia. Methods: Radiographic and ultrasonographic evaluations were performed on 108 hip joints of 54 dogs. Thirty dogs were older than 2 years and 24 were aged between 4 and 10 months. Results: It was verified that an increase in pectineus muscle stiffness (cutoff value > 2.77 m/s) by elastography in some dysplastic dogs and an increase in the thickness of the joint capsule (cutoff value > 0.9 mm) in B-mode ultrasonography, were associated with a distraction index > 0.5, with both having a positive correlation. In B-mode ultrasonographic evaluation, the presence of signs of degenerative joint disease, such as irregularities of the cranial edge of the acetabulum and femoral head, were associated with a distraction index > 0.5 in canines, with a specificity of 94%. In adult dogs, the findings of degenerative joint disease on ultrasound were associated with a diseased OFA classification (P < 0.05). Measurement of the joint capsule > 1.10 mm was diagnostic for dysplasia in unhealthy dogs by OFA. Conclusions: ARFI elastography has shown that the pectineus muscle may experience changes in stiffness in dysplastic animals. Additionally, changes in joint capsule thickness can be identified in B-mode in young and adult dogs with dysplastic joints, which contributes to the diagnosis of hip dysplasia.
Keywords: Acoustic radiation force impulse; Canine; Canine hip dysplasia; Hip laxity; Ultrasonography